Kinerja Angkutan Umum Dinamis Bus Trans Metro Dewata Pada Masa dan Pasca Pandemi - I Gusti Putu Adi Gunayasa; Gede Sri Edi Susanto; I Gede Putu Riyan Adhi Pratama; Irfan Saputra; Luh Ade Gihan Ayu Wijaya; Made Indira Pramesti (PT Ilmu Data Indonesia, 2024)
Transportation is an inseparable part of human life as it plays a crucial role in the distribution of goods, the movement of people, and commodities as micro components of the economy. Transportation is a key element in the economy as it is related to the distribution of goods, services, and labor, and it forms the core of economic activities in urban areas. Various forms of public transportation with different characteristics and levels of service offered, influence the development of urban public transportation systems. This research aims to evaluate the operational performance of public transportation in providing standard services to its passengers. It is expected that the results of this survey will be beneficial for the Government, especially those who manage public transportation in the districts of Tabanan, Badung, and Denpasar. Thus, it can be concluded that Public Transportation in these areas still meets the established operational performance standards.